Genetic Differentiation, Mating Systems and Crossability of Three Floral Variants of Sandalwood (Santalum album L.) in Gunung Sewu Geopark, Indonesia - Indrioko, S; Nurcahyani Cahyaningrum, Y W (KnE Life Sciences, 2019)
Despite the degradation in their origin in the south-eastern islands of Indonesia, sandalwood (Santalum album L.) recently occurs as new landraces in Gunung Sewu Geopark, Java island, Indonesia. All of the landraces consisted of three floral variants (YBF, refers to ‘yellow big flower’; RBF, ‘red big flower’; and RSF, ‘red small flower,’ respectively), which were differed in floral structures. Isoenzymes and hand-pollination treatments were combined to analyze whether these variants have different genetic diversity, mating systems, and crossing ability. Observed heterozygosity varied significantly with sites (H